Defining Subthreshold PTSD in the DSM-IV Literature. Issue 8 (August 2015) - Franklin, C. Laurel; Piazza, Vivian; Chelminski, Iwona; Zimmerman, Mark
<x xml:space="preserve">Abstract</x> Abstract Subthreshold posttraumatic stress disorder (PTSD), whether due to absence of symptom development or partial remission, is the subject of research and clinical work despite being absent from the DSM. A problem with the literature is that subthreshold definitions are inconsistent across studies and therefore aggregating results is difficult. This study compared the diagnostic hit rates and validity of commonly used definitions of Subthreshold PTSD in a single sample. Three definitions of Subthreshold PTSD were extracted from the literature and two were formed, including a model of DSM-5 PTSD-criterion sets, and a definition that requires six or more PTSD symptoms, but no particular criterion set. Participants (N = 654) with a criterion A stressor, but without full PTSD diagnosis, were included. Most individuals did not meet any definition of Subthreshold PTSD. Findings are discussed in light of previous research and need for increased understanding of the diagnostic implications of Subthreshold PTSD.